Sex-Associated Differences in Neurovascular Dysfunction During Ischemic Stroke - Tang, Tianchi; Hu, Libin; Liu, Yang; Fu, Xiongjie; Li, Jianru; Yan, Feng; Cao, Shenglong; Chen, Gao (Frontiers in Molecular Neuroscience, 2022)
Neurovascular units (NVUs) are basic functional units in the central nervous system and include neurons, astrocytes and vascular compartments. Ischemic stroke triggers not only neuronal damage, but also dissonance of intercellular crosstalk within the NVU. Stroke is sexually dimorphic, but the sex-associated differences involved in stroke-induced neurovascular dysfunction are studied in a limited extend. Preclinical studies have found that in rodent models of stroke, females have less neuronal loss, stronger repairing potential of astrocytes and more stable vascular conjunction; these properties are highly related to the cerebroprotective effects of female hormones. However, in humans, these research findings may be applicable only to premenopausal stroke patients. Women who have had a stroke usually have poorer outcomes compared to men, and because stoke is age-related, hormone replacement therapy for postmenopausal women may exacerbate stroke symptoms, which contradicts the findings of most preclinical studies. This stark contrast between clinical and laboratory findings suggests that understanding of neurovascular differences between the sexes is limited. Actually, apart from gonadal hormones, differences in neuroinflammation as well as genetics and epigenetics promote the sexual dimorphism of NVU functions. In this review, we summarize the confirmed sex-associated differences in NVUs during ischemic stroke and the possible contributing mechanisms. We also describe the gap between clinical and preclinical studies in terms of sexual dimorphism.